2020
DOI: 10.1001/jamaoncol.2020.1260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Osimertinib and Bevacizumab on Progression-Free Survival for Patients With Metastatic EGFR-Mutant Lung Cancers

Abstract: IMPORTANCEThe combination of erlotinib and bevacizumab as initial treatment of epidermal growth factor receptor (EGFR [OMIM 131550])-mutant lung cancers improves progression-free survival (PFS) compared with erlotinib alone. Because osimertinib prolongs PFS compared with erlotinib, this trial was designed to study the combination of osimertinib and bevacizumab as first-line treatment.OBJECTIVES To determine the safety and tolerability of osimertinib and bevacizumab combination treatment and assess the 12-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 26 publications
9
85
0
Order By: Relevance
“…FLAURA2 is a phase III randomized trial underway to determine if combining osimertinib with carboplatin/pemetrexed improves PFS and OS (ClinicalTrials.gov accessed on 22 March 2021 Identifier NCT04035486). Antiangiogenic agents are also being pursued (ClinicalTrials.gov accessed on 22 March 2021 Identifier NCT04181060) with a recent publication suggesting bevacizumab and osimertinib led to a favorable 1-year PFS [ 24 ] and other trials that are ongoing as well are trials adding the anti-angiogenic agentand ramucirumab (ClinicalTrials.gov accessed on 22 March 2021 Identifier NCT03909334). Studying the NLR in patients treated with angiogenic agents would also be useful in light of recent FDA approval of ramucirumab with erlotinib in front-line treatment of metastatic NSCLC with EGFR exon 19 deletions or exon 21 (L858R) mutations [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…FLAURA2 is a phase III randomized trial underway to determine if combining osimertinib with carboplatin/pemetrexed improves PFS and OS (ClinicalTrials.gov accessed on 22 March 2021 Identifier NCT04035486). Antiangiogenic agents are also being pursued (ClinicalTrials.gov accessed on 22 March 2021 Identifier NCT04181060) with a recent publication suggesting bevacizumab and osimertinib led to a favorable 1-year PFS [ 24 ] and other trials that are ongoing as well are trials adding the anti-angiogenic agentand ramucirumab (ClinicalTrials.gov accessed on 22 March 2021 Identifier NCT03909334). Studying the NLR in patients treated with angiogenic agents would also be useful in light of recent FDA approval of ramucirumab with erlotinib in front-line treatment of metastatic NSCLC with EGFR exon 19 deletions or exon 21 (L858R) mutations [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…also reported that clearing of all EGFR cfDNA after osimertinib treatment predicts the efficacy of Osimertinib with significant improvement in PFS, ORR, and DCR in 82 patients with NSCLC using Cobas ® EGFR mutation test v2 ( 27 ). Another study showed that cfDNA presence at 6 weeks correlated with short PFS and OS in a phase 1/2 study of osimertinib plus bevacizumab as first-line therapy for advanced EGFR-mutant NSCLC using the QX200 BioRad PCR system ( 28 ). Buder A et al.…”
Section: Discussionmentioning
confidence: 99%
“…No regular scheduled brain imaging regardless of +/-brain mets Sample size: Data at 50% maturity will provide 90% power, 2-sided 5% significance level of "significant" PFS improvement Coordinating principal investigators: Pasi Jänne, David Planchard, Kunihiko Kobayashi FLAURA2 (NCT04035486) Schema arm osimertinib plus bevacizumab combination trial similar to the mPFS achieved by osiemritnib in AURA3. 93…”
Section: Addressing Unmet Needmentioning
confidence: 99%